Consumer expectation and responses to environmental sustainability initiatives and their impact in foodservice operations: A systematic review. Issue 6 (12th July 2021) - Sullivan, Vanessa S.; Smeltzer, Madison E.; Cox, Gregory R.; MacKenzie‐Shalders, Kristen L.
Abstract: Background: With increasing pressure on the Earth's finite resources, there is significant demand for environmentally sustainable practices in foodservice. A shift to sustainable foodservice operations can decrease its environmental impact and may align with consumer expectations. This systematic review explored consumer expectations (attitudes pre‐intervention) and responses (behaviour, cognitive attitudes and affective attitudes post‐intervention) towards environmentally sustainable initiatives of foodservice operations. Methods: A systematic search following PRISMA guidelines was conducted across MEDLINE, EMABASE, CINAHL and Web of Science databases. English and full‐text research articles published up to November 2019 were identified. Consumers' expectations and responses to interventions were extracted. The quality of the studies was assessed using the Mixed Methods Appraisal Tool (MMAT). Results: Thirty‐three studies were included and, given the heterogeneity of the studies, the results were synthesised narratively. The main outcomes analysed included changes in behaviour and attitudes (cognitive and affective), including knowledge and satisfaction. Intervention strategies were interpreted and categorised into three groups: food waste reduction, single‐use item and packaging waste reduction, and initiatives related to menu, messaging and labelling. Most studies resulted in significant pro‐environmental changes towards decreasing food waste, decreasing single use‐item and packaging waste, as well as engaging consumers in sustainable eating. Conclusions: There are a range of successful environmentally sustainable strategies that when implemented by foodservices can have a mostly positive impact on consumer attitudes and responses. However, positive consumer attitudes did not always translate to changes in behaviour. Foodservices should carefully consider implementing interventions that support changes in consumer behaviour. Abstract : This research aims to explore consumer expectations and responses, specifically consumer behaviours, attitudes and satisfaction, towards environmentally sustainable initiatives of foodservices. This systematic review has identified a range of successful environmentally sustainable strategies that can be incorporated by foodservices and appear to have a mostly positive impact on consumer attitudes and satisfaction. However, positive consumer attitudes did not always translate to behaviour change.